Penguatan Kapasitas Hukum Bagi Orang Tua Siswa dan Guru di Desa Kalisegoro Semarang dalam Rangka Peningkatan Kesadaran Tanggungjawab Pendidikan Bersama (Sebuah Pengabdian Pendekatan Hak Asasi Manusia - Arifin, Ridwan; Widyawati, Anis; Rasdi, Rasdi; Wicaksono, Sonny Saptoajie; Maskur, Muhammad Azil (Jurnal Pengabdian Hukum Indonesia, 2019)
Education is a fundamental right that is included in the human rights paradigm (right to education). Education is also one of the indicators of human development (human development index), so education has an important position in people’s lives. One of the problems in the field of education, especially in Indonesia is the awareness of the importance of the implementation of education not only for teachers and students but also parents of students. Many cases of teacher reporting on disciplining students at school become a separate problem, especially for teachers. On the one hand the teacher applies its own learning method which is often disliked by students, even some methods are considered as a form of hard learning, which ends with teacher reporting by parents of students. Another problem is the ignorance and lack of understanding of parents of students on the responsibility of shared education. Kalisegoro Village itself has strategic education access. However, these educational problems still occur, so the need for strengthening legal capacity for parents of students and teachers in dealing with educational problems. Through a program of strengthening legal capacity for students and teachers in the village of Kalisegoro Semarang in order to increase awareness of the responsibility of shared education, it is expected to increase parents' participation in educational assistance for their children, as well as increase teacher understanding regarding various potential problems that may arise and how to solve it. This program is a Criminal Law Service Program, using a human rights approach, where education is an important part of human rights (right to education). This program will involve the Fatayat Nahdhatul Ulama organization Kalisegoro Village and Lecturer in the Faculty of Law, Semarang State University. This program will be addressed to teachers and parents of TPQ students An-Nur Kalisegoro and Fayatat Nahdhatul Ulama Kalisegoro Semarang.